Chebyshev series approximation for solving differential-algebraic equations (DAEs) - Celik, Ercan; Yeloglu, Turgut (TAYLOR & FRANCIS LTD, 2006)
The numerical solution of differential-algebraic equations (DAEs) using the Chebyshev series approximation is considered in this article. Two different problems are solved using the Chebyshev series approximation and the solutions are compared with the exact solutions. First, we calculate the power series of a given equation system and then transform it into Chebyshev series form, which gives an arbitrary order for solving the DAE numerically.
Keywords: differential-algebraic equations; power series; Chebyshev series; approximation; RUNGE-KUTTA METHODS; NUMERICAL-SOLUTION; SYSTEMS; Mathematics